DEVELOPMENT OF THE BLOCK DIAGRAM FOR MEASURING POWER QUALITY AND THE SAMPLING CONTINUOUS PERIODIC SIGNALS (Municipal economy of cities. Series: «Economy science», 2013)
The problems of the development of methods and devices increase the accuracy of measurements.